Digital Currency in Russia: Legal Foundations and Business Implications - Yu. V. Brisov; L. A. Abbasova (Цифровое право, 2024)
The rapid progress of technology and increasing globalization have led to various outcomes in the financial market. This commentary delves into an effort to incorporate digital financial instruments into Russia’s legal framework, with particular focus on the digital ruble. The potential introduction of this digital asset aims to address contemporary economic challenges by restructuring the Russian financial system. The commentary focuses on the legal features and business implications associated with the introduction of the digital ruble, placing it within the broader context of digital assets and their potential impact on the Russian economy. In their methodology, the authors rely on a formal legal, technologically efficient, and systemic approach. The commentary outlines the constraints on possible transformations dictated by the regulatory framework accompanying the introduction of the digital ruble and influenced by the economic nature of digital currency. The article concludes that, while digital financial assets could become a vital part of economic transactions, their introduction should be approached with great caution, and under vigilant oversight of the Bank of Russia. The anticipated integration of the digital ruble is expected to positively affect the market but taking a balanced approach considering the legal, economic, and technological risks for businesses is crucial. Through an examination of the foundations of emerging legal regulation of digital financial assets and their economic characteristics, the authors have devised a ‘digitalization matrix’ — a comprehensive management model for integrating digital technologies into both the commercial and public sectors. The model proposes taking a matrix-based approach to managing digitalization processes, while underscoring the significance of pursuing a thorough and scientifically grounded strategy for implementing digital currencies.